Intimate partner violence among HIV-positive women in discordant relationships attending care and treatment clinics in Dar es Salaam, Tanzania - Milka Mathania; Nathanael Sirili (Frontiers Media S.A., 2023)
BackgroundIntimate partner violence (IPV) toward women is a public health concern affecting many countries across the world. Globally, 30% of women experience lifetime physical, sexual, or psychological harm. HIV-positive women in discordant relationships are at higher risk of experiencing IPV than other women. This study aimed to determine the magnitude and factors associated with intimate partner violence among HIV-positive women in discordant relationships attending HIV care and treatment clinics in Dar es Salaam, Tanzania.MethodsAn analytical cross-sectional study was conducted among 411 HIV-positive women who were in discordant relationships attending HIV care and treatment clinics in eight selected healthcare facilities in Dar es Salaam from June 2021 to July 2021. A questionnaire with structured questions on social-demographic information and factors associated with intimate partner violence was used. Data were collected electronically using the Open Data Kit (ODK) system, cleaned, and stored. Descriptive analysis was done and presented in frequency distribution and cross-tabulation. A chi-square was used to determine the differences in variables, and the modified Poisson regression model was used to estimate adjusted prevalence risk ratios (APRRs) with 95% CI for factors associated with IPV. Variables were considered statistically significant at 95% CI and p < 0.05. All statistical analyses were conducted using STATA version 15.ResultsThe mean age of the participants was 36.2 (standard deviation [SD] ±7.8). The majority of women had attained primary education, i.e., 237 (57.7%). Over 65.7% of HIV-positive women in discordant relationships had ever experienced IPV. Women whose partners had primary and secondary education, were alcohol users, and were solely decision-makers in the family were strongly associated with IPV.ConclusionClose to two-thirds of HIV-positive women who were in discordant relationships attending HIV care and treatment clinics in selected healthcare facilities in Dar es Salaam had ever experienced at least one form of IPV. Low level of education of the partner, alcohol use, and power relation in decision-making were significantly associated with IPV. We recommend routine screening of IPV for HIV-positive women who are in discordant relationships attending HIV care and treatment clinics. Joint efforts are needed in addressing the factors associated with IPV in discordant couples.